The Role of Public Administration in Promoting Citizen Participation in Government Policy - Akhmad Riduan (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Citizen participation in policymaking is a fundamental element of democratic governance. In Indonesia, however, participation often remains symbolic due to limited access to information, weak accountability mechanisms, and a lack of public trust. This study explores the vital role of public administration in enhancing meaningful citizen involvement in government policy formulation and implementation. Using a qualitative method through literature review, the study synthesizes recent scholarly findings and government reports published between 2020 and 2025. It focuses on key themes such as ethical governance, bureaucratic reform, digital innovation, and public communication strategies. Findings show that public administration serves as a mediator, facilitator, and implementer of participatory processes. Ethical governance—marked by integrity, transparency, and accountability—emerged as a precondition for trust and engagement. Decentralization enhances responsiveness at the local level, though it also introduces disparities across regions depending on administrative capacity. Technological innovations such as e-governance and digital platforms foster greater transparency and real-time citizen feedback, yet digital literacy gaps and institutional inertia pose significant challenges. Moreover, effective communication between government and citizens, particularly in the context of economic literacy, is crucial for participatory governance. The study highlights successful case examples from Bandung and Tanjungpinang where digital and community-based models improved policy responsiveness. It concludes that optimizing the role of public administration is essential to advance inclusive, accountable, and responsive governance in Indonesia.